Effect of different concentration of 6- benzyl amino purine (BAP) on shoot multiplication of shoot tip explant of F1 hybrid rock melon (Cucumis melo. L) - Che Mat, Nazila (2017)
Cucumis melo L. which belonging to the family Cucurbitaceae is conventionally propagated by seeds. Low rate of seeds germination, expensive seeds for F1 hybrid and lacking of good parent materials for hybridization are the major problems faced by commercial growers. In vitro propagation method is the best way to produce large number of planting materials and under aseptic condition in controlled environment. The objective of this study was to determine the best concentration of BAP on multiple shoot formation from shoot tip explants of F1 hybrid rock melon. The experimment was conducted Randomized Complete Block Design (RCBD). The seed of F1 hybrid rock melon were germinated aseptically under in vitro conditions in order to obtain its shoot tip. The shoot tip was used to induce shoot multiplication under in vitro condition. The shoot tip was cultured in Murashige and Skoog (MS) medium supplemented with different concentration of BAP (0.0, 0.5, 1.0, 2.0, 5.0 and 10.0 mg/L). All treatment produced between 50- 100% shoot formation after 7 weeks culture. Treatment BAP concentration at 1.0 mg/L induced the highest mean number of shoots per explant.